FAMILY EDUCATION IN RUSSIA AND ABROAD - L. Khalyapina (Вестник Северо-Кавказского федерального университета)
The article deals with the key definitions adopted in the domestic and foreign theory and practice, such as «family education», «home schooling», «home education», revealed their significant differences. The analysis of the legal basis, approaches to the organization offamily education in Russia, USA, Canada and Europe is presented. The article analyzes the practice of family education in Russia and abroad, describes the problems and variations of the organization of family education, the risks of using alternative forms of General education outside the educational organization, as well as ways to overcome them. Considerable attention is paid to the study of diferent points of view on the reasons for the choice of parents home schooling, performance indicators and the feasibility of this form of education.